The environmental impact of green trade and circular trade: Does urbanization matter? - Dorothea M. Ramizo; Helen Cabalu; Mark Harris; Julian Inchauspe (Cleaner Production Letters)
Urban areas are responsible for approximately two-thirds of global energy consumption and over 70% of greenhouse gas emissions, making them pivotal in addressing the global climate crisis. International efforts to achieve decarbonization have emphasized the role of trade in circular economy goods (or circular trade) and green trade composed of environmental goods and low-carbon technologies. Despite their significance, there is limited empirical evidence on how such trade impacts environmental outcomes, particularly when considering urbanization. This study addresses this research gap. Drawing on data from 54 economies between 2000 and 2018, the research employs a panel model incorporating theoretical transmission mechanisms and non-linear threshold effects. The findings reveal that while circular trade reduces environmental degradation, green trade initially exacerbates it. However, interaction models show that urbanization mitigates these negative impacts, enabling green trade to deliver better environmental outcomes. Panel threshold analysis supports these findings. These results challenge the prevailing narrative that green trade mitigates environmental degradation, shedding light on the complex dynamics between trade, urbanization, and environmental sustainability. This study highlights the need for tailored policies that consider a country’s urbanization level to maximize the environmental gains of green and circular trade.